Descemet's stripping automated endothelial keratoplasty with anterior chamber intraocular lenses: complications and 3-year outcomes. Issue 8 (27th March 2014) - Ang, Marcus; Li, Lim; Chua, Daniel; Wong, Cheewai; Htoon, Hla M; Mehta, Jodhbir S; Tan, Donald
Abstract : Purpose: To describe outcomes and complications following Descemet's stripping automated endothelial keratoplasty (DSAEK) in eyes with pseudophakic bullous keratopathy (BK) while retaining the anterior chamber intraocular lenses (ACIOL). Methods: We included consecutive patients who underwent DSAEK for BK at a single tertiary centre from 1 January 2008 to 1 April 2010, from our prospective cohort (Singapore Corneal Transplant Study). We compared eyes with BK, which underwent DSAEK while retaining ACIOL (n=18), to those with DSAEK alone with the posterior chamber intraocular lenses left in place as a comparison group (n=114). Main outcome measures were endothelial cell (EC) loss and graft survival. Results: The percentage EC loss at 1 year was 31.9±21.3% in the DSAEK with ACIOL group compared to 24.5±21.2% in the DSAEK group (p=0.516); however, this figure was significantly greater in the DSAEK with ACIOL group at 3 years compared to the DSAEK group (55.3±29.2% vs 33.3±20.8%; p=0.01 respectively). Graft survival was also significantly poorer in the DSAEK ACIOL group compared to the DSAEK group over 3 years (log rank p=0.002). Conclusions: We found that although eyes with BK and ACIOL that underwent DSAEK while retaining the ACIOL suffered EC loss which was not significantly greater at 1 year, EC loss and graft survival were significantly poorer compared to DSAEK controls at 3 years postoperatively.